Effect of Using Bagasse Ash and Glass Powder on Concrete Compressive Strength - Syafwandi, Syafwandi; Sulistyawan, Latif (NAROTAMA UNIVERSITY, Indonesia, 2020)
Bagasse ash is a waste from the sugar factory industry which has silica content and grain size is relatively the same as cement. Glass powder is made from industrial glass and household waste, has a silica content and grain size is relatively same as sand. The use of both wastes as concrete substitutes is expected to reduce environmental pollution and exploitation of natural resources. This study aims to determine the effect of bagasse ash as a cement substitution and glass powder as sand substitution in a concrete mixture on the compressive strength. This study uses a mixture of bagasse ash 2.5%, 5%, and 7.5% by weight of cement, and the glass powder is 5%, 10%, and 15% by weight of sand. Compressive strength testing on days 7 and 28. The results of this study are the higher percentage of substitution materials, workability will decrease. Compressive strength testing shows that all variations have resulted under normal concrete. The highest compressive strength is obtained from variation A with a mixture of 2.5% bagasse ash + 5% glass powder that is 24.50 MPa. Variation of the mixture with bagasse ash of 2.5% has a higher compressive strength than other variations on day 28.